O Clube da Quarta-feira - Martins, José de Souza (2003)
A chronicle of the life of Trinity Hall, one of the oldest Colleges of the University of Cambridge (England), and of the meeting with one of its oldest fellows, the Educator Lionel Elvin, who taught Raymond Williams and Robin Maughan and who socialized with Karl Mannheim, Harold Laski, R.H. Tawney and John Maynard Keynes.